Eastern Caribbean Currency Union : 2009 Discussion on Common Policies of Members Countries; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
The Eastern Caribbean Currency Union (ECCU) countries financial system has increasingly come under stress particularly through weakly supervised nonbank and offshore financial sectors with knock-on effects to domestic banks. The staff report focuses on ECCU's 2009 discussion on common policies of member countries on economic development and policies. In response, ECCU authorities have accelerated the establishment of national Single Regulatory Units and the passage of harmonized legislation to strengthen then regulation and supervision of nonbanks and offshore institutions.